Role of wearable rhythm recordings in clinical decision making—The wEHRAbles project. Issue 9 (22nd July 2020) - Manninger, Martin; Kosiuk, Jedrzej; Zweiker, David; Njeim, Mario; Antolic, Bor; Kircanski, Bratislav; Larsen, Jacob M.; Svennberg, Emma; Vanduynhoven, Philippe; Duncker, David
Abstract: Background: Multiple wearable devices for rhythm analysis have been developed using either photoplethysmography (PPG) or handheld ECG. Hypothesis: The aim of this survey was to assess impact of these technologies on physicians' clinical decision‐making regarding initiation of diagnostic steps, drug therapy, and invasive strategies. Methods: The online survey included 10 questions on types of devices, advantages, and disadvantages of wearable devices as well as case scenarios for patients with supraventricular arrhythmias and atrial fibrillation (AF). Results: A total of 417 physicians (median age 37 [IQR 32‐43] years) from 42 countries world‐wide completed the survey. When presented a tracing of a regular tachycardia by a symptomatic patient, most participants would trigger further diagnostic steps (90% for single‐lead ECG vs 83% for PPG, P < .001), while a single‐lead ECG would be sufficient to perform an invasive EP study in approximately half of participants (51% vs 22% for PPG, P < .001). When presented with a single‐lead ECG tracing suggesting AF, most participants (90%) would trigger further diagnostic steps. A symptomatic AF patient would trigger anticoagulation treatment to a higher extent as an asymptomatic patient (59% vs 21%, P < .001). PPG tracings would only rarely lead to therapeutic steps regardless of symptoms. Most participants would like scientific society recommendations on the use of wearable devices (62%). Conclusions: Tracings from wearable rhythm devices suggestive of arrhythmias are most likely to trigger further diagnostic steps, and in the case of PPG recordings rarely therapeutic interventions. A majority of participants expect these devices to facilitate diagnostics and arrhythmia screening but fear data overload and expect scientific society recommendations on the use of wearables.